2021
DOI: 10.3390/toxins13030227
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Single and Combined Toxicity of Chlorantraniliprole and Bacillus thuringiensis (GO33A) against Four Selected Strains of Plutella xylostella (Lepidoptera: Plutellidae), and a Gene Expression Analysis

Abstract: Concerns about resistance development to conventional insecticides in diamondback moth (DBM) Plutella xylostella (L.), the most destructive pest of Brassica vegetables, have stimulated interest in alternative pest management strategies. The toxicity of Bacillus thuringiensis subsp. aizawai (Bt GO33A) combined with chlorantraniliprole (Chl) has not been documented. Here, we examined single and combined toxicity of chlorantraniliprole and Bt to assess the levels of resistance in four DBM strains. Additionally, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 54 publications
0
8
0
3
Order By: Relevance
“…The LC 50 values for Bt-G033A, CL, and mixture insecticide (Bt + CL) were significantly higher in FOH-DBM and resistant strains (Bt-DBM, CL-DBM, and BtC-DBM) compared to SS-DBM strain. The resistance level of these DBM strains is different due to different generations of the strains from the results of our previous article ( Shabbir et al, 2021 ). The results revealed that Bt-G033A was the most toxic to all the DBM strains among the tested insecticides.…”
Section: Resultsmentioning
confidence: 68%
See 3 more Smart Citations
“…The LC 50 values for Bt-G033A, CL, and mixture insecticide (Bt + CL) were significantly higher in FOH-DBM and resistant strains (Bt-DBM, CL-DBM, and BtC-DBM) compared to SS-DBM strain. The resistance level of these DBM strains is different due to different generations of the strains from the results of our previous article ( Shabbir et al, 2021 ). The results revealed that Bt-G033A was the most toxic to all the DBM strains among the tested insecticides.…”
Section: Resultsmentioning
confidence: 68%
“…A high-resistant strain of DBM was collected from the Shijing county of Guangdong province in 2017 and named as FOH-DBM. Detailed information with respect to insecticide resistance of FOH-DBM is given in Supplementary Figure 1 and also discussed in our previous manuscript ( Shabbir et al, 2021 ). Later, this population was established in the greenhouse and reared on cabbage without exposure to insecticide.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The CYP6AE76 activity was assessed according to the method reported by Qian et al [ 74 ] and Shabbir et al [ 75 ] with slight modification. A 125 μL of 2 mM p-nitroanisole (p-NA) solution and 50 μL (0.5 mg/mL) cytochrome P450 monooxygenase expressed in E. coli were added to each well of a microplate and mixed.…”
Section: Methodsmentioning
confidence: 99%